ONRECHTMATIG OVERHEIDSDAAD BY THE GOVERNMENT ON THE LIABILITY OF THE GOVERNMENT REGULATION (CASE STUDY ON LAW NUMBER 18 OF 2017) - Khafifah, Nur Rizqi; Minan, Ahsanul; Rusydi, Muhammad (Fakultas Hukum Universitas Padjadjaran, 2023)
This paper discusses about